Aplicación de Irradiación Gamma a salamín picado fino: Efecto en su estabilización durante el almacenamiento - Raad, Angela; Cingolani, María Celeste; Lires, Carla María Laura; Soteras, Trinidad; Buffoni Almeida, Mariana Ines; Grisaro, Agustina; Pawlak, Sandra Eva; Vogt, María Verónica; Cova, María Constanza; Vaudagna, Sergio Ramon (Asociación Argentina de Tecnólogos Alimentarios - AATA, 2024)
Listeria monocytogenes (Lm) is one of the pathogens most frequently detected in dry fermented sausages and difficult to control in the production environment. The Argentine Food Code (CAA) establishes the zero tolerance criterion for Lm. In this work, gamma irradiation was applied as a technology to eliminate Lm in Salamín Picado Fino (SPF) and the possibility of extending the storage time of the stabilized product was studied. Samples of industrial SPF were used, prepared with pork and beef, starter culture, bacon, salt, sugar, spices and wine. After 10 days of drying and maturation (fresh SPF), the salamins were peeled, vacuum packed (100 μm polyamide/EVOH/polyethylene bag) and stored at 4.0±0.5 °C for 24 h until irradiated. Gamma irradiation was carried out in conservators at 5±2 °C in the Co-60 Semi-Industrial Irradiation Plant of the Ezeiza Atomic Center at 4, 6 and 8 kGy, dose rate of 13 kGy/h. The treated and control salamins were stored at 4.0±0.5 ºC until analyzed at 0, 30, 60, 90 and 120 days post-irradiation. Doses were selected based on radiosensitivity in SPF calculated from D10 (decimal reduction dose) values ​​of Lm ATCC-15313 (0.75 kGy) and a cocktail of Lm strains isolated from contaminated meat products (0.73 kGy) obtained inprevious tests. A minimum absorbed dose (Dmin) of 4 kGy was estimated as 5xD10 to achieve the objective, and 6 kGy (1.5xDmin) and 8 kGy (2xDmin) were chosen to evaluate a possible maximum tolerable dose (Dmax). A preliminary sensory analysis with Trained panelists ruled out 8 kGy due to negative impact on sensory quality. HE performed microbiological analyzes for Lm research (ISO 11290-1:1996- Amd:2004) and counts of enterobacteria (ICMSF), sulfite-reducing anaerobes (ISO 15213:2003) and lactic acid bacteria (LAB) (AOAC-PTM-041701). The analysis Statistical analysis was done with a two-factor design (dose, storage time and interaction) with Kruskall Wallis tests (p<0.05) and t-Student (p<0.05). The Sensory attributes were analyzed with a panel of 8 evaluators trained using a difference test compared to a control (fresh SPF) and the samples by the consensus method. The results were analyzed statistically using the bilateral Dunnett test. In all doses and times of storage, the absence of Lm/25g was observed and the counts of enterobacteria and sulphite-reducing anaerobes were <10CFU/g. BAL count [Log(CFU/g)] to 0 kGy during storage was between 6.3±0.2/8.2±0.3 and those irradiated between 2.8±0.3/3.4±0.1; with significant effects of dose and dose-time interaction. storage (p<0.05), but not significant for time (p>0.05). The analysis sensory did not show an effect from the treatment at 4 kGy up to 90 days, but it did at 6 kGy from 0 days. The application of gamma irradiation at 4 kGy as a method of Lm control allows obtaining a microbiologically suitable product, with a count of BAL of 44% compared to the control at 0 days that increases during storage providing a flavor similar to that of the non-irradiated product, with a 90-day stabilization under refrigeration conditions; 30 more days compared to product currently marketed.